Teacher-Centred and Teacher Controlled Learning: A Postmodernism Perspective - Misdi, Misdi; Hartini, Nurani; Farijanti, Dian; Wirabhakti, Agus (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2013)
The role of teachers in learning is central. It greatly influences the success and the quality of learning process. Yet, it remains lack of evidences in some areas such as diminishing the learners' learning automony. Lamguage learners are positioned lower than the teachers. In decentralized learning, teachers are facilitators. As the result of this point of views, the learners are less appreciated for their imperfect learning behaviours for some reasons regarding for their potentials. Thus, this article is to criticize and to elaborate the evidences of teacher-centred learning and teacher-controlled learning in postmodernism paradigm and the realities in Indonesian efl perspectives which emphasizes on the main actors in learning and the power of learning. Yet, there is no absolute truth in terms of power in learning.